Role of Bumdes in the Management of Spiritual Tourism Objects in Petilasan Sumur Kembar, West Bali National Park - Ni Made Puspasutari Ujianti; A.A Sagung Laksmi Dewi; Hartini Saripan; Gautam Kumar Jha (Fakultas Hukum, Universitas Warmadewa, 2022)
The new paradigm of tourists in the last 10 (ten) years greatly affects the attractions visited by both foreign and domestic tourists. Tourists who used to only want to enjoy natural beauty, culinary, and night tours, now there is a change in the orientation of tourist destinations. Tourists now prefer to travel to villages with panoramic views and village culture, tourists miss seeing the beautiful village atmosphere and Balinese culture which is still very thick with the nuances of Hinduism. Bali, known as the Thousand Temples, is very rich in religious places and temples that used to be a place of yoga for holy people. Likewise with Jembrana Regency which is geographically with the East Java Island which is very thick with its Javanese culture. Along the coast of the Bali Strait and West Bali National Park, there are many petilasan which is a stopover and hermitage place for holy people who sailed from the ancient Mataram Kingdom and Islamic Mataram who expanded to Bali. One of them is the Petilasan of Sumur Kembar Temple and Petilasan of Mbah Temon which are located in the Cekik Forest area, Gilimanuk Village. To further introduce and more professional management of tourist objects, in accordance with the policy of the Department of Tourism and Culture of Jembrana Regency, the management is handed over to BUMDes. So that income from tourism objects managed through BUMDes is to increase the source of Village Original Income, which of course will be used to improve the welfare of the Village community.